PENGARUH PEMBERIAN REBUSAN DAUN SIRIH MERAH TERHADAP KEPUTIHAN PATOLOGIS PADA REMAJA PUTRI - Sri Wulan (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
Pathological leucorrhoea is a vaginal discharge that occurs due to a bacterial infection, a fungus in which the fluid that comes out a lot and continuously from the vagina and the color of the liquid is not clear or white or yellow or greenish. This study aims to determine the effect of giving red betel leaf decoction to pathological vaginal discharge in young women in Merbau 1 High School. This study used a quasy experimental design, purposive sampling technique, and a sample of 46 people in which 23 were in the intervention group and 23 were in the control group. The sheet pre test and post test is an instrument in this study which contains signs and symptoms of vaginal discharge. The increase in the incidence of leucorrhoea from 2 female students who experienced mild vaginal discharge to moderate vaginal discharge in the control group showed that red betel leaf decoction water was able to overcome pathological vaginal discharge compared to normal water. Based on the results of the Wilcoxon test means that there is an effect of giving red betel leaf stew to pathological vaginal discharge in young women in Merbau 1 High School. Researchers suggested that health workers, especially nurses, be able to introduce more about the benefits of red betel leaf decoction to the community, especially women, so that people were more confident in using non-pharmacological treatments.